Implementasi Kebijakan Pemberdayaan Penyandang Masalah Kesejahteraan Sosial (Studi pada Dinas Sosial Kota Malang) - Febryan, Fourry Ade (Jurnal Administrasi Publik, 2016)
Abstract: Implementation of Empowerment Social Welfare Problems Policy (Study in The Department of Social Services in Malang City). Problem of Social Welfare show up there are citizen who not compiled with right for their base necessary as if, because there are not acquire the Social Services from this State. To overcome problem of social welfare Government territory of Malang City through Social Service Department have to publish some of the policy arrangement in order to strategic policy Social Services Department in 2014 have to proclaim some policies which is one of the policy are Empowerment Social Welfare Policy. Results of this study show up that Implementation of process Empowerment Social Welfare Problem is worked, but still found some problems in implementation. In communication, Socialization policy already carried out. Social Service Department in Malang City have the human resource, infrastructure resources, and sufficient budget. To support the continuity quality policy, in this research also show up the attitude inclination of implementer policy or authorizing signature from Social Service Department in Malang City to carrying out Implementation Policy is not optimal. In other side there are supporting factors of the policy among the clear base of law, the clear communication between the actors, as well as funding support. However, this realization is obstruct by the limited personnel / workforce of social welfare, yet there is a database of social welfare, and the weakness of the socialization of social welfare legislation to the institutions and the society. Keywords: Implementation, Problem of Social Welfare, Policy Abstrak: Implementasi Kebijakan Pemberdayaan Penyandang Masalah Kesejahteraan Sosial (Studi pada Dinas Sosial Kota Malang). Permasalahan kesejahteraan sosial dewasa ini menunjukkan bahwa masih terdapat warga negara yang hak atas kebutuhan dasarnya belum terpenuhi secara layak dikarenakan belum memperoleh pelayanan sosial dari negara. Untuk mengatasi permasalahan Penyandang Masalah Kesejahteraan Sosial tersebut, Pemerintah Daerah Kota Malang melalui Dinas Sosial telah mengeluarkan beberapa kebijakan yang dituangkan serta diatur dalam Rencana Strategis Dinas Sosial Kota Malang, dimana salah satu kebijakan tersebut adalah Pemberdayaan Penyandang Masalah Kesejahteraan Sosial. Hasil dari penelitian ini menunjukkan bahwa proses Implementasi Kebijakan Pemberdayaan Penyandang Masalah Kesejahteraan Sosial telah berjalan, namun masih ditemukan beberapa kendala dalam pelaksanaannya. Dalam aspek komunikasi sosialisasi kebijakan telah terlaksana dengan baik. Dinas Sosial Kota Malang telah memiliki sumber daya manusia, sumber daya sarana dan prasarana, serta anggaran yang cukup untuk mendukung kelancaran dilaksanakannya kebijakan. Dalam penelitian ini juga menunjukkan disposisi dari Dinas Sosial Kota Malang dalam pelaksanaan Implementasi Kebijakan masih kurang. Disisi lain, terdapat faktor pendukung kebijakan, diantaranya terdapat landasan hukum yang jelas, komunikasi antar aktor yang jelas, serta adanya sumber dana yang mendukung. Namun pelaksanaan ini terhambat oleh keterbatasan personil / tenaga kerja kesejahteraan sosial, belum terdapat database bidang kesejahteraan sosial, serta lemahnya sosialisasi undang-undang kesejahteraan sosial kepada lembaga dan masyarakat. Kata Kunci: Implementasi, Masalah Kesejahteraan Sosial, Kebijakan